Correction: Nutritional targeting modification of silkworm pupae oil catalyzed by a smart hydrogel immobilized lipase. Issue 24 (3rd December 2021) - Wang, Jin-Zheng; Wu, Cheng-Kun; Yan, Cheng-Hai; Chen, Huan; You, Shuai; Sheng, Sheng; Wu, Fu-An; Wang, Jun
Abstract : Correction for 'Nutritional targeting modification of silkworm pupae oil catalyzed by a smart hydrogel immobilized lipase' by Jin-Zheng Wang et al., Food Funct., 2021, 12, 6240–6253, DOI: ; 10.1039/D1FO00913C .